2009
DOI: 10.1038/nnano.2009.353
|View full text |Cite
|
Sign up to set email alerts
|

Label-free biomarker detection from whole blood

Abstract: Label-free nanosensors can detect disease markers to provide point-of-care diagnosis that is low-cost, rapid, specific and sensitive.1-13 However, detecting these biomarkers in physiological fluid samples is difficult because of problems like biofouling and nonspecific binding, and the resulting need to use purified buffers greatly reduces the clinical relevance of these sensors. Here, we overcome this limitation by using distinct components within the sensor to perform purification and detection. A microfluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
328
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 508 publications
(339 citation statements)
references
References 28 publications
1
328
0
2
Order By: Relevance
“…I). [74][75][76][77]80] At the end of this review, we will discuss in details that recent progresses on operating GFETs at high frequencies suggested that Debye screening can be overcome: [46] 1.…”
Section: Debye Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…I). [74][75][76][77]80] At the end of this review, we will discuss in details that recent progresses on operating GFETs at high frequencies suggested that Debye screening can be overcome: [46] 1.…”
Section: Debye Screeningmentioning
confidence: 99%
“…Possible routes to circumvent the Debye screening effect include short antibody design, porous polymer incorporation, and ex situ measurement in low ionic strength buffers (see Section 2.5). [74][75][76][77]80] These approaches, however, also impose limitations on the biodetection and it is highly desirable to develop a straightforward methods to overcome the Debye screening: [46] 1. without any special design or engineering of the receptor molecules and the sensor environments, and 2. in physiological conditions to facilitate in-situ, real-time biosensing. Theoretically, improved sensitivity is expected at high frequencies using a measuring strategy that overcomes the ionic screening effect.…”
Section: Overcoming the Debye Length Limitations With Radio-frequencymentioning
confidence: 99%
“…1(b). The NW surfaces were functionalized with a monolayer of APTES (3-aminopropyltriethoxysilane) using the protocol described earlier, 11 which increases device stability and reduces gate leakage current in solution. A fluidic well was then glued on top of each chip for the sensing experiments, with a platinum wire used as the solution gate electrode.…”
mentioning
confidence: 99%
“…Таким образом, разработка новых подходов для регистрации белка с концентрационной чувствительностью (DL) на уровне DL<10 -12 М [28,33,34] является актуальным направлением в области протеомного анализа и медицинской диагностики.…”
unclassified
“…Как видно, имеется существенное расхождение результатов экспериментов с данными расчётов по вышеуказанным моделям, описывающим вылавливание белка на поверхность чипа. Известны и другие примеры [33,47,48], в которых сообщается о достижении DL=2,8´10 -14 М для белка PSA при использовании нанопроводного детектора. Время регистрации белка на поверхности наноразмерного чипа при этом составило менее 20 мин.…”
unclassified